Rapid response of stage IV colorectal cancer with APC/TP53/KRAS mutations to FOLFIRI and Bevacizumab combination chemotherapy: a case report of use of liquid biopsy - Alexander Hendricks; Philip Rosenstiel; Sebastian Hinz; Greta Burmeister; Christoph Röcken; Kathrin Boersch; Clemens Schafmayer; Thomas Becker; Andre Franke; Michael Forster (BMC, 2020)
Abstract Background Liquid biopsies of blood plasma cell free DNA can be used to monitor treatment response and potentially detect mutations that are present in resistant clones in metastatic cancer patients. Case presentation In our non-interventional liquid biopsy study, a male patient in his fifties diagnosed with stage IV colorectal cancer and polytope liver metastases rapidly progressed after completing chemotherapy and deceased 8 months after diagnosis. Retrospective cell free DNA testing showed that the APC/TP53/KRAS major clone responded quickly after 3 cycles of FOLFIRI + Bevacizumab. Retrospective exome sequencing of pre-chemotherapy and post-chemotherapy tissue samples including metastases confirmed that the APC/TP53/KRAS and other major clonal mutations (GPR50, SLC5A, ZIC3, SF3A1 and others) were present in all samples. After the last chemotherapy cycle, CT imaging, CEA and CA19-9 markers validated the cfDNA findings of treatment response. However, 5 weeks later, the tumour had rapidly progressed. Conclusion As FOLFIRI+Bevacizumab has recently also been associated with sustained complete remission in a APC/TP53/KRAS triple-mutated patient, these driver genes should be tested and monitored in a more in-depth manner in future patients. Patients with metastatic disease should be monitored more closely during and after chemotherapy, ideally using cfDNA.